EDUKASI KESEHATAN CEGAH KECEMASAN DAN STRES KEPADA REMAJA DI ERA PANDEMI COVID-19 DI SMP BUDI MULIA, BOGOR - Yunita Astriani Hardayati; Hany Wihardja (UNIVERSITAS KHAIRUN, 2022)
Covid-19 is a disease caused by the SARS-CoV-2 virus and has become a global pandemic due to it’s rapid spread. Every citizen is required to limit mobility to prevent the spread of disease. The learning system from home is one of the government’s strategies to prevent the spread in the age group of children and adolescents. Changes in the learning system have positive and negative impacts on students. The negative impact that can arise is feelings of stress in adolescents and if not managed properly it can escalate into a state of severe anxiety to panic. SMP Budi Mulia fully applies online learning methods for students. The solution that we can offer so that students can learn effectively is education to prevent anxiety and stress. This community service aims to improve the knowledge and skills of SMP Budi Mulia students to manage the anxiety and stress. The method used is a persuasive participatory method with education and practice activities through the Zoom Cloud Meeting platform. The results that have been achieved are increasing knowledge of the concepts of anxiety and stress, identifying anxiety levels using SRQ and HAM-A instruments and increasing stress prevention skills in adolescents. This education is very important for adolescents focusing on mental health to support their physical health and quality of life.